1985
DOI: 10.1002/macp.1985.021860117
|View full text |Cite
|
Sign up to set email alerts
|

α,ω‐dichloropoly(2‐methylpropene) as an inifer: A modification to the Kennedy‐Smith mechanism

Abstract: Experimental details are given of attempts to enumerate the binary ionogenic equilibria (B.I.E.) of i-chloro-1-methylethylbenzene (l)/BC13, 1,4-bis(l-chloro-l-methylethyl)benzene (2)/BCI3 and 1,3,5-tris(l -chloro-I methylethy1)benzene (3)/BCI3 in CH2C12. Due to chemical reaction (dimerisation or polymerisation) no experimental values for the B.I.E. constants could be obtained. A Born-Haber cycle is constructed to estimate the relative sequence of the overall B.I.E. constants. A similar treatment for 2-chloro-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Rate depressions have been observed in other living isobutylene polymerization systems that use electron donors. 2,[20][21][22][23][24][25][26][27][28] Several hypotheses have been forwarded to explain the rate depressions observed in these systems. 2,20-28 A likely reason for the observed rate depression is a decrease in the effective concentration of Me 2 AlCl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rate depressions have been observed in other living isobutylene polymerization systems that use electron donors. 2,[20][21][22][23][24][25][26][27][28] Several hypotheses have been forwarded to explain the rate depressions observed in these systems. 2,20-28 A likely reason for the observed rate depression is a decrease in the effective concentration of Me 2 AlCl.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the rate depression is quite surprising, considering the amount of dimethyl phthalate added to the system. Rate depressions have been observed in other living isobutylene polymerization systems that use electron donors. , Several hypotheses have been forwarded to explain the rate depressions observed in these systems. , A likely reason for the observed rate depression is a decrease in the effective concentration of Me 2 AlCl. A similar explanation is used for observed rate depressions in TiCl 4 -based living isobutylene polymerizations carried out in the presence of Lewis bases …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was shown that 2-chloro-2,4,4-trimethylpentane (i.e. the hydrochlorinated dimer of isobutene) ionized with TiCl 4 was an efficient initiator in the cationic polymerization of isobutene. , The extent of ionization, i.e., the concentration of the initiating cation, depends also on the respective natures of Lewis acid and of the leaving group.…”
Section: Introductionmentioning
confidence: 99%
“…Puskas et al 4 concluded that ion pairs are the chain carriers in the living polymerization of isobutylene. Alternatively, Nuyken 7 regarded unpaired ions as the active species in his tertiary chloride/ BCl 3 system. Since the equilibrium constant of ionization (K i ) k ion /k c < 10 -5 L/mol) is regarded to be very low for isobutylene polymerization, the concentration of ionized species is also very low.…”
Section: Introductionmentioning
confidence: 99%